Group formation and voter participation - Helios Herrera; Cesar Martinelli (Theoretical Economics, 2006)
We present a model of participation in large elections in which the formation of voter groups is endogenous. Partisan citizens decide whether to become leaders (activists) and try to persuade impressionable citizens to vote for the leaders' preferred party. In the (unique) pure strategy equilibrium, the number of leaders favoring each party depends on the cost of activism and the importance of the election. In turn, the expected turnout and the winning margin in an election depend on the number of leaders and the strength of social interactions. The model predicts a nonmonotonic relationship between the expected turnout and the winning margin in large elections.
Keywords: D72; 330; Voter mobilization; endogenous leaders; turnout; winning margin